Effectiveness of Science Technology Engineering Mathematics Problem Based Learning (STEM PBL) and Science Technology Engineering Mathematics Project Based Learning (STEM PjBL) to Improve Critical Thinking Ability - Putri Syntia Monika; Suharno Suharno; Lita Rahmasari (Postgraduate, University of Mataram, 2023)
This research sought to compare the effectiveness of Science Technology Engineering Mathematics Problem Based Learning (STEM PBL) and Science Technology Engineering Mathematics Project Based Learning (STEM PjBL) learning models in fostering critical thinking abilities. Quantitative research with a pretest posttest comparison group design is the methodology employed. Based on the outcomes of an investigation of normal and homogeneous data. The increase falls into the high category because the average N-gain value for STEM PjBL on all facets of critical thinking skills is 0.76. STEM PBL, however, is 0.66, thus the growth is in the middle range. The independent t-test results revealed that there was a difference between the two courses in the development of critical thinking abilities, with sig. (2-tailed) of 0.01. The study's findings indicate that both STEM PjBL and STEM PBL can be utilized to enhance critical thinking abilities, but STEM PjBL is more beneficial in this regard.